2014
DOI: 10.1016/j.jde.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Concentrating standing waves for the fractional nonlinear Schrödinger equation

Abstract: Abstract. We consider the semilinear equationis a sufficiently smooth potential with inf R V (x) > 0, and ε > 0 is a small number. Letting w λ be the radial ground state of (−∆) s w λ + λw λ − w p λ = 0 in H 2s (R N ), we build solutions of the formwhere λ i = V (ξ ε i ) and the ξ ε i approach suitable critical points of V . Via a Lyapunov Schmidt variational reduction, we recover various existence results already known for the case s = 1. In particular such a solution exists around k nondegenerate critical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
224
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(229 citation statements)
references
References 31 publications
3
224
0
2
Order By: Relevance
“…By using the Lyapunov-Schmidt reduction method, they showed that (1.6) has a nontrivial solution u ε concentrating to some single point as ε → 0. In [11], assuming that f (x, t) = |t| p−2 t and V is a sufficiently smooth potential with inf R N V > 0, Dávila et al recovered various existence results already known for the case α = 1 and showed the existence of solutions around k nondegenerate critical points of V for (1.6). In [30], Shang and Zhang studied the concentration phenomenon of solutions for (1.6) under the assumptions f (x, t) = K(x)|t| p−2 t, V , K are positive smooth functions and inf R N V > 0.…”
Section: Introduction and Main Resultsmentioning
confidence: 87%
“…By using the Lyapunov-Schmidt reduction method, they showed that (1.6) has a nontrivial solution u ε concentrating to some single point as ε → 0. In [11], assuming that f (x, t) = |t| p−2 t and V is a sufficiently smooth potential with inf R N V > 0, Dávila et al recovered various existence results already known for the case α = 1 and showed the existence of solutions around k nondegenerate critical points of V for (1.6). In [30], Shang and Zhang studied the concentration phenomenon of solutions for (1.6) under the assumptions f (x, t) = K(x)|t| p−2 t, V , K are positive smooth functions and inf R N V > 0.…”
Section: Introduction and Main Resultsmentioning
confidence: 87%
“…Very recently, in [13], Dávila, del Pino and Wei generalized various existence results known for (1.4) with s = 1 to the case of fractional Laplacian. In [23], the authors gave a result which says that (1.4) with V (x) being radial has solutions with large number of bumps near infinity and the energy of this solutions can be very large when ε is fixed and N ≥ 2.…”
Section: Introductionmentioning
confidence: 91%
“…For more related study, the interested reader may consult [24][25][26][27][28][29][30][31][32][33][34] and the references therein. It should also be noted that the concentration phenomena for the fractional Schrödinger equation have been investigated byDávila, del Pino et al [35,36], and Fall, Mahmoudi and Valdinoci [37].…”
Section: Introductionmentioning
confidence: 99%